2018
DOI: 10.1016/j.appet.2017.11.099
|View full text |Cite
|
Sign up to set email alerts
|

Independent and interactive associations of negative affect, restraint, and impulsivity in relation to binge eating among women

Abstract: There is growing recognition that impulsivity may serve as an underlying risk factor for binge eating. In addition, the association of impulsivity with binge eating may be moderated by other affective and cognitive risk factors. This study examined independent and interactive associations of negative affect, dietary restraint, and facets of impulsivity with binge eating. A diverse sample of 566 undergraduate women completed online questionnaires of study variables. Results revealed a three-way interaction of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 67 publications
3
23
0
Order By: Relevance
“…Overall, the present study confirmed the importance of individual difference factors, such as negative affect, and situational factors, such as familiar location, and absence of others in disordered eating [32,46]. In particular, it seems that individuals who engage in DE tend to use food in situations where they experience high levels of negative affect, and are without others to socialise and interact with, possibly for comfort or coping purposes [8]. As such, this was the first study to demonstrate that there are within-person situational processes in disordered…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Overall, the present study confirmed the importance of individual difference factors, such as negative affect, and situational factors, such as familiar location, and absence of others in disordered eating [32,46]. In particular, it seems that individuals who engage in DE tend to use food in situations where they experience high levels of negative affect, and are without others to socialise and interact with, possibly for comfort or coping purposes [8]. As such, this was the first study to demonstrate that there are within-person situational processes in disordered…”
Section: Discussionsupporting
confidence: 80%
“…Extant literature appears insufficient in investigating DE in normal population, but a number of studies have found that certain psychological factors (i.e., low selfesteem [3], negative affect [4,5], impulsivity [6]) and contextual factors (i.e., eating with or without other people [7]) might increase the risk of DE [8]. However, these risk factors are often studied individually and little is known about how they might interact.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it may reflect facets of impulsivity, which has recently been associated with binge eating. For example, the association between negative affect and binge eating was found to be strengthened by higher levels of non-planning impulsivity ( Mason et al, 2018 ). Other facets of impulsivity, such as reward sensitivity or delay discounting, may also trigger thoughts about ‘ eating and loss of control .’…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent research also indicates the presence of comorbidity between BE and the use of alcohol and binge drinking in young people (Kessler et al, 2013; Laghi et al, 2014; Fouladi et al, 2015). Impulsivity has also been positively associated with BE (Steward et al, 2017; Mason et al, 2018) and could play an important role in the comorbidity between disordered eating behavior and excessive alcohol consumption in young students (Ocampo et al, 2012). Finally, a significant positive association between BE and BMI and obesity has consistently been observed.…”
Section: Introductionmentioning
confidence: 99%